Assessment of knowledge regarding menstruation and sanitary absorbents among young women of Haryana - Mor, Preeti Nain; Kumari, Vinod (International Journal Of Community Medicine And Public Health, 2022)
Background: Aim of the study was to access the knowledge regarding menstruation and sanitary products among young women from rural, urban and slum areas of Gurugram and Nuh. Methods: A comparative cross-sectional study was conducted among 240 young women of Gurugram and Nuh districts of Haryana, India with the help of a pre-designed semi-structured interview schedule. Data were analyzed using MS-Excel. Chi-square test, Pearson’s correlation and two sample t-test were used as statistical tools to analyze the data. Results: The overall level of knowledge regarding menstruation was found to be poor among 84.2 percent of women from Nuh and 49.2 percent from Gurugram. The findings of the study revealed that education of respondents and their mother, occupation of respondent, socio-economic status, mass media exposure and religion etc. were highly significantly associated with level of knowledge regarding menstruation. Knowledge regarding menstruation was found positively correlated with menstrual hygiene practices (r=0.545** in Gurugram and r=0.270* in Nuh) and with the general perceptions regarding menstruation (r=0.500** in Gurugram and r=0.256* in Nuh) respectively. A significant difference was observed in the knowledge regarding menstruation of women from rural, urban and slum areas of Gurugram and Nuh. Conclusions: Women still lacked of proper knowledge about this crucial phenomenon of their body which leads to various unhygienic menstrual practices and misconceptions about menstruation. Knowledge of young women can be improved through education interventions on menstruation and its importance in their life.